Intrasite Spatial Analysis of Mobile and Semisedentary Peoples : Analytical Approaches to Reconstructing Occupation History - Gingerich, Joseph A. M.; Clark, Amy E. (Amy Elizabeth) 1983- (Book collections on Project MUSE., 2022)
"In the 1980s and early 1990s, a number of studies were published on intrasite spatial analysis following a surge of ethnoarchaeological work from the previous decade. Many of these publications were edited volumes "that dealt with the arrangement of artifacts within individual archaeological horizons from a range of site types" and were focused on mobile peoples (huntergatherers). They are now at least thirty years old. This volume focuses on current studies and new offerings of intrasite spatial analysis. During the intervening years, different approaches to intrasite spatial analysis were developed based on "higher quality data, technological innovations, and a more sophisticated understanding of what processes govern spatial patterning in the archaeological record.""--